Combining Ability and Agronomic Performance of Diallel Crosses of Low-Nitrogen Tolerant Maize Inbred Lines - Aboderin Olawale Serifdeen; Oyekunle Muhyideen; Olakojo Oloruntoba Olatayo; Ebini Isa Ahmed; Abubakar Adamu Masari; Olajide Olasunkanmi (Agriculture, 2024)
Low soil nitrogen (N)-tolerant inbred lines often possess advantageous genetic traits that confer resilience in N-deficient environments, making them suitable for developing high-yielding hybrids. This study assessed the combining ability of 11 low-N-tolerant inbred lines and the agronomic performance of their diallel hybrids under low-N and non-stressed conditions to identify hybrids adapted to N stress. Significant general combining ability (GCA) effects (p < 0.01) were observed for all traits under both conditions, with GCA accounting for over 78% of the total variation, indicating the predominance of additive genetic effects. Specific combining ability (SCA) effects were non-significant and weakly correlated with yield. Meanwhile, GCA showed strong correlations with yield (r = 0.57, p < 0.01), highlighting its reliability as a predictor of hybrid performance. Based on GCA values, line SMLW-156 emerged as a valuable genetic resource for breeding early-maturing, high-yielding hybrids, while SMLW-99 showed promise for producing hybrids with shorter plant and ear heights. The low-N tolerance index identified 78.2% of hybrids as tolerant, while the selection index based on trait points classified all hybrids as tolerant to varying degrees, demonstrating the effectiveness of low-N-tolerant inbred lines as parent materials. Hybrids SMLW-156 × SMLW-159 and SMLW-99 × SMLW-156 achieved the highest yields of 8,508 kg/ha and 8,250 kg/ha, respectively, with yield advantages of 6.3% and 7.5% over standard checks. The high yield, stability, and heterotic advantage for stay-green traits of SMLW-156 × SMLW-159 position it as a strong candidate for further testing and potential commercialization across diverse Nigerian environments.